Experimental Design Validation of Tilting Calibration Mechanism by Using Shape Memory Alloy Spring Actuator - Hyun-Ung Oh; Myeong-Jae Lee; Taegyu Kim (International Journal of Aerospace Engineering)
A tilting calibration mechanism is periodically deployed to view the reference temperature target during on-board calibration of a spaceborne imaging sensor and stowed after calibration. In the present work, we have proposed a new design strategy using a shape memory alloy (SMA) spring as an actuator that provides a fail-safe function to prevent the blocking of the main optical path when the mechanical driving part of the mechanism is stopped at a certain position during on-board calibration. Although a launch locking device was not considered in the design, this approach makes it possible to impose mechanical constraints on the driving part of the mechanism in severe launch vibration environments. The effectiveness of the proposed design was experimentally validated by a deploying and stowing function test and launch vibration environment tests such as a sine burst test, a random vibration test, and a pyroshock simulating impulse shock test. The test results demonstrated that the mechanism fulfills all the required functions for on-board calibration. The use of an SMA spring actuator was proved effective for implementing the dual function of a fail-safe in an emergency phase and a mechanical constraint on the driving part of the mechanism in severe launch vibration environment.